2021
DOI: 10.1186/s40337-021-00414-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the contextual body image questionnaire for athletes: a replication and extension study in female collegiate athletes

Abstract: Background Although the link between body dissatisfaction and eating disorder (ED) pathology is well-established in general female samples, less is known about contextual body image (CBI) among female athletes. CBI refers to female athletes’ body image concerns in two contexts: sport and daily life. The Contextual Body Image Questionnaire for Athletes (CBIQA) measures four dimensions of body image (Appearance, Thin-Fat Self-Evaluation, Thin-Fat Others’ Evaluation, and Muscularity) in both conte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The questionnaire has been found to be positively correlated with the Body Image and Body Change Inventory [18], the Body Areas Subscale of the Multi-dimensional Body-Self Relations Questionnaire [19], and the Somatomorphic Matrix [20]. The validity of the CBIQA has also been confirmed by Stewart et al [21], who showed that in a sample of 52 high-level female athletes, different body image dimensions relating to either the daily life or sport context, determined eating disorders and negative mood/behaviours. Using the CBIQA, Danckers [22] found that athletes had a different body image in the context of daily life compared with that in sport.…”
Section: Introductionmentioning
confidence: 72%
“…The questionnaire has been found to be positively correlated with the Body Image and Body Change Inventory [18], the Body Areas Subscale of the Multi-dimensional Body-Self Relations Questionnaire [19], and the Somatomorphic Matrix [20]. The validity of the CBIQA has also been confirmed by Stewart et al [21], who showed that in a sample of 52 high-level female athletes, different body image dimensions relating to either the daily life or sport context, determined eating disorders and negative mood/behaviours. Using the CBIQA, Danckers [22] found that athletes had a different body image in the context of daily life compared with that in sport.…”
Section: Introductionmentioning
confidence: 72%